Kebijakan Sekolah terhadap Penggunaan Gadget dalam Pembelajaran IPS Terpadu - Diah Nuril Azizah; Muhammad Syafiq Humaisi (Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to determine the use of gadgets in Integrated Social Studies learning in class VII C of SMP Ma'arif 1 Ponorogo and to determine the implementation of school policies in the use of gadgets in SMP Ma'arif 1 Ponorogo. This study uses a qualitative research method in which the data collected in the form of words, pictures and not numbers like quantitative research. The data analysis technique in this study uses inductive analysis and the type of research is case study. Data was collected by using interview, observation and documentation techniques. The technique of checking the validity of the data is done by triangulation of sources and triangulation of techniques. The data analysis technique uses the Miles and Huberman model analysis technique by using the steps of reducing data, presenting data, and drawing conclusions. The results of this study indicate that the use of gadgets in class VII C SMP Ma'arif 1 Ponorogo in integrated social studies learning functions as a learning facility that is used to work on questions, look for material that has not been understood and look for integrated social science material that is not in the book, gadgets at the time of writing. Lesson hours may not be used but are still under the supervision of the teacher.